Vision of nursing scholars in relation to the aging process - Medeiros, Fabíola de Araújo Leite; Rodrigues, Ranielly Pereira Lacerda; Nóbrega, Maria Miriam Lima da (Rev Rene, 2012)
The aim of this study was to examine the perception of student’s nursing related to the aging process and to reflect in reformulation of higher nursing’s education. The data were collected from two institutions of higher nursing education in Brazil, from August 2009 to July 2010, with the participation of 84 college students. After the analysis three thematic categories were found: 1) Aging refers to the vital stage of weakness and needs special care; 2) Aging is a natural process of life cycle; 3) The process of aging is a phase that requires more attention and social participation. The results showed that there is a need to plan actions of teaching and research within the focus of gerontology, breaking the taboos surrounding old age and focus on healthy aging.